2018
DOI: 10.3390/polym10030341
|View full text |Cite
|
Sign up to set email alerts
|

Lignocellulose-Chitosan-Multiwalled Carbon Nanotube Composites with Improved Mechanical Strength, Dimensional Stability and Fire Retardancy

Abstract: A novel composite composed of lignocellulose (LC), glutaraldehyde crosslinked chitosan (GC) and multiwalled carbon nanotube (MWCNT) was fabricated by the hot-pressing process. The effect of the additional GC and MWCNT on the mechanical strength, dimensional stability and fire retardancy of lignocellulose composites was investigated. The results showed that LC/GC/MWCNT composite exhibited the maximum modulus of rupture (MOR) of 35.3 MPa, modulus of elasticity (MOE) of 2789.1 MPa and internal bonding (IB) streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 57 publications
(70 reference statements)
0
8
0
Order By: Relevance
“…18 1.6.5.1 Carbon nanotube A wide range of studies have shown that carbon nanotubes (CNTs) either single-walled (SWCNTs) or multiwalled (MWCNTs) are among the most promising alternatives for traditional flame retardants to be used in different polymers, such as, PP, PE, PLA, lignocellulose, epoxy resin. [84][85][86][87][88] These studies have demonstrated that adding a small amount of well-dispersed CNTs (<5 wt%) to polymer composites can significantly improve the fire behavior due to their fascinating chemical and physical properties. 89 CNTs have a highly elongated structure with a large aspect ratio.…”
Section: Carbon Family Based Additivesmentioning
confidence: 99%
See 2 more Smart Citations
“…18 1.6.5.1 Carbon nanotube A wide range of studies have shown that carbon nanotubes (CNTs) either single-walled (SWCNTs) or multiwalled (MWCNTs) are among the most promising alternatives for traditional flame retardants to be used in different polymers, such as, PP, PE, PLA, lignocellulose, epoxy resin. [84][85][86][87][88] These studies have demonstrated that adding a small amount of well-dispersed CNTs (<5 wt%) to polymer composites can significantly improve the fire behavior due to their fascinating chemical and physical properties. 89 CNTs have a highly elongated structure with a large aspect ratio.…”
Section: Carbon Family Based Additivesmentioning
confidence: 99%
“…85,90 Moreover, low flame spread rate, smoke-suppression, and anti-dripping properties have been reported while incorporating CNTs in different polymers. 86,87 Improvement in fire retardancy of polymer composites is strongly dependent on uniform dispersion of CNTs and their interactions with the polymer matrix. 84,89 There are different surface modification methods and fabrication techniques, supporting CNTs homogenous distribution in polymers.…”
Section: Carbon Family Based Additivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Medium density fiberboards were prepared according to our previous studies [ 5 ]. In a typical process, a mixture of 2% ( w / v ) was obtained by dissolving chitosan in an acetic acid solution of 1.5% ( w / v ) at room temperature for 2 h under stirring.…”
Section: Methodsmentioning
confidence: 99%
“…This is due to their abundance, low cost, and easy machinability [ 1 , 2 ]. In general, the fiberboards exhibit hydrophilic, hygroscopic, and flammable properties during application due to the existence of abundant hydroxyl groups in the wood fiber surface, their porous structure, and organic nature [ 3 , 4 , 5 ]. This sensitivity to humidity changes and flame usually results in a decrease in the service life of fiberboards and a threat to the human safety.…”
Section: Introductionmentioning
confidence: 99%